ANALISA KUALITAS BAHAN BAKAR JENIS PERTALITE DI SPBU DENGAN PERTALITE DI PERTAMINI BERDASARKAN PARAMETER UJI SPECIFIC GRAVITY, REID VAPOUR PRESSURE, DOCTORT TEST, DISTILASI, COPPER STRIP TEST, OCTANE NUMBER - Rahma Nuryanti; Dian Kurnia Sari; Inta Marlen Puspita Sari (Journal of Innovation Research and Knowledge, 2023)
Pertalite is a type of fuel with 90-octane level which is used for four- wheeled and two-wheeled vehicles. This study compares the quality of Pertalite fuel at Gas Stations (SPBU) with Pertamina Mini (Pertamini). The aim of the research is to compare the quality of pertaline sold in different places. The parameters used in this research were specific gravity ASTM D-1298 which showed specific gravity 60/60 "F of 0.718 for Gas Station A, 0.719 for Gas Station B, 0.720 for Gas Station C 0.720 at Pertamini A, 0.731 at Pertamini B, and 0.730 at Pertamini C. Then, distillation ASTM D-86 on temperature 90% marked the values of 210 °C, 210°C. 178 °C, and 183 C. Reid vapour pressure ASTM D-323 results were 7.1 Psig. 7.6 Psin. 65 Psig. 7.1 Psig. 3.5 Psig, and 2.9 Psig. Doctor test IP-30 showed the results negative, negative, negative, slightly positive, slightly positive, negative." Copper strip test ASTM D-130 showed the results of 1b, 3b, 2a, 2a, 3h, and 2h. The last test, the octane number ASTM D-2699, showed the results of 90, 89.4, 90, 80, 764, and 87. The results of this study indicated that the values of some parameters for pertalite at gas stations met the spec values, while various test parameters for pertalite ut Pertamini were off spec. It is suggested that the quality of pertalite meet the criteria for the analysis results according to the standard provisions